On the complexity of the ideal of absolute null sets - Zakrzewski, P. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Answering a question of Banakh and Lyaskovska, we prove that for an arbitrary countable infinite amenable group G the ideal of sets having μ-measure zero for every Banach measure μ on G is an F_σ δ subset of {0,1}^G.